STUDI LITERATUR KEPEMIMPINAN PEMBERDAYAAN DALAM KAJIAN FILSAFAT ILMU - Isnanda Zainur Rohman; Mugi Harsono (MANAJEMEN DEWANTARA, 2023)
This study examines empowering leadership from the perspective of philosophy (ontology, epistemology, and axiology). The method used in this research is a literature review method by explaining the history, theory, and previous studies. The aim of this study is to investigate the construct of leadership in philosophy of science. This study also provides the development of leadership theories and practices. This study indentifies the antecedents and consequences of empowerment leadership. The antecedents of empowerment leadership are neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness (big 5 personality factors). The consequence of empowerment leadership is leader effectiveness.